Willingness to pay for product ecological footprint: Organic vs non-organic consumers - Limnios, E.; Schilizzi, S.; Burton, M.; Ong, A.; Hynes, Niki (Elsevier Inc., 2016)
The problem of environmental degradation is large and widespread, with consumption of food being a major contributor to a households' ecological impact. The Product Ecological Footprint (PEF) is a new information management process of “self-improving” accuracy that enables producers to quantify product environmental impact. This study addresses two key questions; consumer willingness to pay and application readiness for PEF. We use choice experiments to identify the value consumers place on PEF as a label. We then examine data availability, information processing systems and accreditation protocols that would be required to support a market-wide application of PEF. Findings highlight an opportunity to influence the behaviour of the larger market segment of conventional (non-organic) consumers. Further research is required into the interaction between PEF and organics, PEF and origin, marketing and branding of the label, for market wide applications to be considered. A key question emerges as to whether PEF requires a different application platform than a voluntary eco-label scheme to instigate behavioural change.